Estudo do controle de H2S (sulfeto de hidrogênio) e CO2 (dióxido de carbono) em uma planta de produção de óleo e gás na camada pré-sal - Guedes, Marcus (2012)
The offshore industry is full ascension in Brazil, driven by the discovery of light oil and rich gas abundant in the pre-salt layer. The explored natural gas in the pre-salt layer has superior calorific components, however it has H2S and CO2 (considered acid components) dissolved in its composition. The removal of such components is necessary still in the production field, seeking to fit the gas in the effective specifications for ANP - National Agency of the Petroleum. Nowadays the most used method to remove acid components from the extracted gas of the pre-salt layer is through amine plants. With that comes the need to know the process and to operate it in the most efficient possible way, treating the same amount of gas with the minimum cost. The need for research arises from the difficulty from FPSO Capixaba s operation part to maintain the specifications of the manufacturer s project (VME Process), as the concentration of the amine solvent, amount of treated fresh water and new amine daily added inside the system. To maintain the established project levels it was necessary superior addition both of solvent amine as treated fresh water, showing a removal of H2S and CO2 sometimes satisfactory sometimes not. So, the aim of this investigation was to propose the best possible point of operation for the amine plant in operation in FPSO Capixaba through a study case, between May of 2010 to June of 2012 and was built scatter plots based on historical data to find the ideal concentration that the system operates with the best efficiency on H2S and CO2 removal, using minimum daily addition of amine and treated fresh water. The results were confronted with specifying it in projects and applied, resulting in an economy in order 75,8% amine and 76% of treated fresh water monthly, maintaining the treated gas in the system between of the specifications and effective standards in Brazil. A statistic technique of multiple regressions was built for the study of relationship between the water/amine concentration and of H2S and CO2. It was obtained a total of samples of 245 days for amine concentration (classified as dependent variable) and an equation that esteemed it relationship was built with CO2 and H2S concentration (considered independent variables). The results obtained in the model indicate a good relationship in the estimators studied (R2(adjusted) = 0,8051) and a standard error of 0,029.